A day in the life of a Ménière's patient: understanding the lived experiences and mental health impacts of Ménière's disease. Issue 5 (2nd December 2016) - Bell, Sarah L.; Tyrrell, Jessica; Phoenix, Cassandra
Abstract: Concepts of social practice are increasingly being used to understand experiences of everyday life, particularly in relation to consumption and healthy lifestyles. This article builds on this in the context of lives disrupted and reshaped by chronic illness. It uses social practice theory to examine the lived experiences of individuals with Ménière's disease; a long‐term progressive vestibular disorder, defined by episodes of severe and debilitating vertigo, aural fullness, tinnitus and sensorineural hearing loss. Drawing on the findings of 20 in‐depth narrative interviews with Ménière's patients, and eight spousal/partner interviews, we explore the impacts of the condition on sensory, temporal, spatial and social dimensions of the body. In doing so, we highlight the intensely embodied sensory and emotional work required to maintain connections between the 'competences', 'materials' and 'meanings' that constitute and sustain the performance of both mundane and meaningful social practices over time. As connections between these elements of social practice are disrupted during more active phases of the condition, affected individuals may be defected from old practices and recruited to new ones, often requiring both time and social support to find meaning or pleasure in these alternative ways of being in the world.